Changes in expression of alpha-1, 2 and β-2 adenoidal receptor gene in cumulus cells of infertile women with polycystic ovary syndrome (IVF candidate) and effect of clonidine on it - Farideh Zafari Zangeneh; Elaheh Aboutorabi; Masoumeh Dehghan; Sara Zabihzadeh (Mashhad University of Medical Sciences, 2019)
Introduction: Ovarian function should control follicle development, steroidogenesis, and ovulation processes by ovarian external and internal hormonal signals. Sympathetic system Alpha and beta receptors play a role in regulation of theca and granulosa cells activity for folliculogenesis and steroidogenesis. This study was performed with aim to investigate the changes in expression of alpha 1, 2 and beta 2 adrenergic receptors gene of ovary cumulus in infertile women with polycystic ovarian syndrome (IVF candidate) and effect of clonidine on it. Methods: This case-control study was conducted in 2017 on two groups of control (healthy women donating oocytes) and case (patients with polycystic ovaries). Ovulation induction drugs were prescribed in two groups for ovulation growth. After oocyte puncture, the follicular fluid was collected with cumulus-oocyte collection.  The cumulus cells were isolated by enzyme and were cultured. RNA was then extracted from cumulus cells and its concentration was read by Nano-drop device. cDNA was synthesized and primer was designed for ADRB2 and ADRα1.2 gene expression and the gene expression was assessed by Real-time PCR technique. Finally, the effect of clonidine on protein level of ADRβ2 and ADRα1.2 genes in cumulus cells was investigated by immunocytochemistry technique (western blot) in two groups. Results: The results of this study confirmed: 1) increasing of gene expression level in women with PCOS compared with control group and 2) efficacy of clonidine on gene expression. The severity of the drug efficacy on receptors gene expression was ADRα1 <ADRβ2 <ADRα2, respectively. Conclusion: The results of gene expression and immunocytochemistry showed that clonidine could significantly reduce gene expression of three adrenergic receptors, especially α2 in women with PCO, and therefore clonidine pharmacotherapy could be suggested.